Hydrolytic Stability of Boronate Ester‐Linked Covalent Organic Frameworks. Issue 2 (30th January 2018) - Li, Huifang; Li, Haoyuan; Dai, Qingqing; Li, Hong; Brédas, Jean‐Luc
Abstract: The stability of covalent organic frameworks (COFs) is essential to their applications. However, the common boronate ester‐linked COFs are susceptible to attack by nucleophiles (such as water molecules) at the electron‐deficient boron sites. To provide an understanding of the hydrolytic stability of the representative boronate ester‐linked COF‐5 and of the associated hydrolysis mechanisms, density functional theory (DFT) calculations were performed to characterize the hydrolysis reactions of the molecule formed by the condensation of 1, 4‐phenylenebis(boronic acid) (PBBA) and 2, 3, 6, 7, 10, 11‐hexahydroxytriphenylene (HHTP) monomers; two cases were considered, one dealing with the freestanding molecule and the other with the molecule interacting with COF layers. It was found that the boronate ester (B–O) bond dissociation, which requires one H2 O molecule, has a relatively high energy barrier of 22.3 kcal mol −1 . However, the presence of an additional H2 O molecule significantly accelerates hydrolysis by reducing the energy barrier by a factor of 3. Importantly, the hydrolysis of boronate ester bonds situated in a COF environment follows reaction pathways that are different and have increased energy barriers. These results point to an enhanced hydrolytic stability of COF‐5 crystals. Abstract : Reaction pathways of the hydrolysis of boronate ester‐linked covalent organic frameworks are analyzed based on DFT calculations, using the model molecule comprised two monomer units as an example. Water molecules are found to catalyze the hydrolysis by promoting the proton transfer involved in bond breakage, while COF‐5 crystals have enhanced hydrolytic stabilities.